Spectrophotometric Determination of Dapsone from Pharmaceutical Preparations - Chakravarthy, I.E.; Rami Reddy, N. (Asian Journal of Chemistry, 2016)
A simple spectrophotometric method for determination of dapsone was developed by diazotization of drug followed by addition of ammonia solution. The absorbance of the yellow colour solution developed was measured at 445 nm on Spectronic-1001 spectrophotometer. Beer’s law is obeyed in the concentration range of 0.2–0.6 mg/mL at the wavelength of maximum absorption. Results of analysis were validated statistically and by recovery studies. The method is successfully employed for the determination of dapsone in various pharmaceutical preparations.